Kemanfaatan Digitalisasi Sistem Informasi Akuntansi Dalam Proses Pembelian Dan Pembayaran Diplatform E-Commerce Terhadap Kepuasan Pemakai - Erna Murniati; Natasha Nadira Putri; Zul Azmi (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of digitalization of accounting information systems on user satisfaction in the purchasing and payment process on e-commerce platforms. The objects of the study were students who were already working and using e-commerce platforms such as Shopee, Tokopedia, Lazada, Bukalapak, and TiktokShop. Data were obtained using a survey of 83 respondents. With a quantitative approach, the data was then processed using multiple regression. The results of the study indicate that digitalization of accounting information systems has a positive and significant effect on user satisfaction. In addition, the purchasing and payment process on e-commerce platforms also has a significant impact on user experience and satisfaction. Partially, digitalization of accounting information systems has a significant effect on user satisfaction. The purchasing and payment process on e-commerce platforms also has a significant effect. Simultaneously, digitalization of accounting information systems and purchasing and payment processes have a significant effect on user satisfaction. This study emphasizes the importance of integrating digital technology that supports efficiency and security in transactions. Not only does it have an impact on increasing user satisfaction, but it also contributes to the growth and sustainability of e-commerce platforms in the future.